Çevrecilik Söylemleri Ve Türkiye’deki Çevre Hareketlerinin Seyri / Environmental Discourses and the Course of Environmental Movements in Turkey - Öztürk, Özkan (Journal of History Culture and Art Research, 2017)
Abstract Environmentalism covers a whole of consistent ideological, philosophical and scientific practices for positively reorganizing the unequal relations between nature and society. In its process of historical evolution, the concept of environmentalism has embodied several political, philosophical and economic variables while other factors have lost their impact in the meantime. Therefore, environmentalism has undergone a number of theoretical and practical changes. While discourses of environmentalism configure their directions by relying upon different intellectual grounds, they build their social practices with reference to these political discourses. This study analyzes discursive dimensions of environmentalism and focuses upon the discursive reciprocity of the relation between intellectual arguments and political orientations in social practices. It further discusses the course of environmental movements regarding the values they have produced and concentrates on the socialization processes of environmental movements along with environmental discourses and practices. Öz Çevrecilik, doğa ve toplum arasındaki eşitsiz ilişkilerin olumlu yönde yeniden düzenlenmesi için, kendi içinde tutarlı ideolojik, felsefi ve bilimsel pratiklerin bütününü kapsar. Tarihsel seyri içinde düşünüldüğünde, çevrecilik düşüncesine çeşitli siyasal, felsefi ve ekonomik değişkenler dâhil olurken başka değişkenler önemini kaybetmiştir. Böylece çevrecilik hem teorik anlamda hem de pratikte farklılaşmıştır. Çevrecilik söylemleri birbirinden farklı düşünsel tabanlara yaslanarak siyasal söylemlerinin yönünü tayin ederken toplumsal pratiklerini de bu siyasal söylemler çerçevesinde inşa etmişlerdir. Bu çalışma çevreciliğin söylemsel boyutunu inceleyerek, düşünsel argümanlarla siyasal yönelimler arasındaki ilişkinin toplumsal pratikte nasıl söylemsel bir karşılık bulduğuna odaklanmaktadır. Bununla birlikte Türkiye’deki çevre hareketlerinin seyri çevre söylemlerinin ürettiği değerler içinde ele alınacak ve çevreci hareketlerin toplumsallaşma süreçleri çevre söylemleri ve pratikleriyle beraber değerlendirilecektir.